Influence of Moxifloxacin on Hepatic Redox Status and Plasma Biomarkers of Hepatotoxicity and Nephrotoxicity in Rat - Ayokanmi Ore; Ebenezer Tunde Olayinka (Biochemistry Research International)
Moxifloxacin is a broad spectrum fluoroquinolone antibacterial agent. We examined the hepatic redox status and plasma biomarkers of nephrotoxicity and hepatotoxicity in rat following administration of moxifloxacin (MXF). Twenty-four Wistar rats, 180–200 g, were randomized into four groups (I–IV). Animals in group I (control) received 1 mL of distilled water, while animals in groups II, III, and IV received 1 mL each of MXF equivalent to 4 mg/kg b.w., 8 mg/kg b.w., and 16 mg/kg b.w., respectively. After seven days, plasma urea, bilirubin, and creatinine were significantly (P<0.05) elevated in the MXF-treated animals. Activities of alkaline phosphatase, aspartate aminotransferase, and alanine aminotransferase were significantly increased in the plasma of MXF-treated animals compared to control. Also plasma total cholesterol, HDL-cholesterol, LDL-cholesterol, and triglycerides increased significantly in the MXF-treated groups relative to control. Moreover, MXF triggered a significant decrease in hepatic catalase, superoxide dismutase, and glutathione-S transferase activities. Likewise, MXF caused a decrease in the hepatic levels of glutathione and vitamin C. A significant increase in hepatic MDA content was also observed in the MXF-treated animals relative to control. Overall, our data suggest that the half-therapeutic, therapeutic, and twice the therapeutic dose of MXF induced nephrotoxicity, hepatotoxicity, and altered hepatic redox balance in rats.